Kemampuan Berpikir Komputasi Ditinjau Dari Kecemasan Belajar Matematika - Latifah, Annisa Gina; Quini, Ira Fadriani; Aripin, Usman (Universitas Galuh, 2024)
Mathematics learning is a process of interaction between learning components that aims to improve students' thinking skills and increase their skill to create mathematical concepts in the way they are capable of. Computational thinking is a cognitive skill that students must have to face the development of science and technology in the 21st century, with students having this skill students can know how to define patterns, break down complex problems into smaller parts, organize and make steps to provide solutions, and make data representations through simulations, work coherently on a problem at hand and can master the concept of working on a problem. The purpose of this study was to analyze the skill of computational thinking in terms of high, medium, and low learning anxiety of the research subjects. This research was conducted at SMPN 8 Cimahi Class IX E with descriptive qualitative case study research. Five students from class IX E were the research subjects that we used with high category only one subject then medium category and low category, each with two subjects. The data collection methods in this study were questionnaires, tests, and interviews as well as triangulation techniques. The results of this study showed that two subjects with low learning anxiety showed high and medium results on computational thinking skill, two subjects with low learning anxiety showed high and medium results on computational thinking skill.